The Utilization of By Product of Tapioca Industry on Nata de Cassava Processing : To Study the Addition of Sucrose and Mungbean Sprout - Rifda Naufali; Condro Wibowo (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2004)
By product of tapioca industry, which is an environmental problem, has a potential to be a raw material of nata production due to its high carbohydrate content. Nata is high-fibre food which is an important for the health. The research on which this article was aimed at finding out the potential of by product of tapioca industry as a raw material of nata production by improving the nutrition addition, adding sucrose and mungbean sprout extract. Completely Randomized Design was applied in this research with three replication. The sucrose addition with three levels, namely 2.5, 5 and 7.5% and mungbean sprout extract addition with three levels, namely 0.25, 0.5 and 7.5%. The examined parameters were the contents of water, crude fiber, pH after incubation, thickness, wet rendement, dry rendement and texture. The research concluded that the addition of 7.5% sucrose was the optimum concentration which producing nata with highest wet rendemnet 41.67 % (w/w) and 8.77 mm thick; addition of 0.75 % sprout mungbean extract was optimum concentration producing nata of 41.00 % (w/w) wet rendement and 8.02 mm thick. The best treatment was combination of 7.5 % ucrose and 0.75 mungbean sprout extract addition. Key words : Nata de cassava, sucrose, mungbean sprout extract.